Quantitative microbial risk assessment of salmonellosis from chicken and pork salad consumption in Cambodian households - Chea, Rortana; Sinh Dang-Xuan; Hung Nguyen-Viet; Lindahl, Johanna F.; Grace, Delia; Unger, Fred; Tum, S.; Ty, C.; Boqvist, Sofia (International Livestock Research Institute, 2022)
Introduction: Salmonella is an important foodborne bacterial pathogen that causes high risk to human health globally. Purpose: This study aimed to estimate the risk of Cambodian consumers of acquiring salmonellosis after consuming contaminated chicken and pork salad using a quantitative microbial risk assessment. Methods: Chicken meat and pork samples (n=204 each) were collected from traditional markets in 25 provinces for Salmonella analyses. Practices of cooking chicken and pork salad from 93 Cambodian households were surveyed and used to design an experiment to assess Salmonella cross-contamination from raw meat to ready-to-eat salad. Data on Salmonella contamination, salad consumption and dose response (alpha=0.00853 and beta=3.14) were modelled using Monte Carlo simulations with @Risk at 10,000 iterations. Results: The prevalence of Salmonella in chicken meat and pork were 42.6% (87/204) and 45.1% (92/204) respectively. The average concentration of Salmonella in chicken meat was 10.6 MPN/g, and in pork 11.1 MPN/g. Half of the interviewed households processed and cooked meat for salad directly after purchasing. The QMRA model showed that the annual risk of salmonellosis estimated from consuming chicken salad, pork salad and mixtures of chicken and pork salads were 11.2% (90%CI 0.0 – 35.1), 4.0% (90%CI 0.0 – 21.3), and 14.5% (90%CI 0.0 – 33.5), respectively. The factors with the highest influence on the estimate were cross-contamination while preparing salad, followed by the prevalence of Salmonella on chicken meat and pork at the market. A wide confidence interval in the estimated incidence was mainly due to the variability in the degree of reduction in bacteria concentration by cooking, and salad consumption pattern. Significance: The risk of salmonellosis due to chicken and pork salad consumption appears to be high. Control measures may include improving the safety of retailed chicken and pork at markets and improving hygiene practices and equipment during salad preparation at household.